2020
DOI: 10.2480/agrmet.d-19-00030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on blackthorn (<I>Prunus spinosa</I> L.) phenophases in spring season

Abstract: Phenology is the study of periodic biologic changes that plants are going through, under the influence of environmental factors, especially temperature. The present paper evaluates the behaviour of Prunus spinosa L. genotypes under the fluctuations of climatic factors by calculating the average time elapsed from bud-breaking to blooming, the average time elapsed between different phenophases, the heat demand and the chilling requirement. The data obtained show that the onset of spring season phenological phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Regarding the budding of C. monogyna , Fichtner and Wissemann [ 20 ] report the period from mid-March to April, depending on altitude and location, and the April to June period was reported for the “end of flowering period”. The results obtained within the P. spinosa species are in accordance with those obtained by Cosmulescu and Calusaru Gavrila [ 21 ] in Romania. Regarding the “full flowering” phenophase, taking into account the Julian date, the order in which this phenophase is triggered is as follows: Prunus spinosa (94.67 days); Pyrus pyraster (97.33 days); Malus sylvestris (102.67 days); Crataegus monogyna (123 days); Crataegus pentagyna (138 days); Rosa canina (143 days); Sambucus nigra (146 days); and Rubus caesius (179.67 days).…”
Section: Resultssupporting
confidence: 91%
“…Regarding the budding of C. monogyna , Fichtner and Wissemann [ 20 ] report the period from mid-March to April, depending on altitude and location, and the April to June period was reported for the “end of flowering period”. The results obtained within the P. spinosa species are in accordance with those obtained by Cosmulescu and Calusaru Gavrila [ 21 ] in Romania. Regarding the “full flowering” phenophase, taking into account the Julian date, the order in which this phenophase is triggered is as follows: Prunus spinosa (94.67 days); Pyrus pyraster (97.33 days); Malus sylvestris (102.67 days); Crataegus monogyna (123 days); Crataegus pentagyna (138 days); Rosa canina (143 days); Sambucus nigra (146 days); and Rubus caesius (179.67 days).…”
Section: Resultssupporting
confidence: 91%
“…Support for the FHH is most often associated with observational studies (e.g. Cosmulescu & Calusaru, 2020; Guo et al., 2014). By contrast, experimental studies which manipulate chilling levels beyond historically observed minima in the field tend to support the DSH (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis suggests that reproductive and vegetative buds utilize the same underlying environmental cues, but have different threshold responses to forcing, with whichever bud type bursts later—leaves or flowers—having a higher thermal requirement (i.e. they need a greater sum of warm temperature to trigger the phenological event, Cosmulescu & Calusaru, 2020; Cosmulescu & Ionescu, 2018; Guo et al., 2014). Under this hypothesis, which we call the forcing hierarchy hypothesis (FHH), leaf and flower buds share the same suite of cues and develop similarly to non‐forcing cues (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature, soil Sustainability 2022, 14, 4991 2 of 10 moisture, available nitrogen levels, light, and high levels of carbon dioxide variations affect plant phenology. Among the environmental factors, temperature plays a predominant role in controlling the proper growth and flowering of plants [8][9][10][11][12]. Most of plants require a "hot-cold-hot" sequence to complete their annual cycle [13].…”
Section: Introductionmentioning
confidence: 99%